1981
DOI: 10.1172/jci110160
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal coronary vascular response to exercise in dogs with severe right ventricular hypertrophy.

Abstract: A B S T R A C T Measurements of right coronary artery blood flow, aortic and right ventricular (RV) pressures and heart rate were radiotelemetered during strenuous, spontaneous exercise in normal dogs and dogs with severe RV hypertrophy induced by chronic (5-6 mo) pulmonary artery stenosis. With fixed pulmonic stenosis, dogs with RV hypertrophy exhibited a decrease (P < 0.01) in arterial pressure during exercise. Under these conditions, exercise increased right coronary artery blood flow and decreased right co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
6
0

Year Published

1983
1983
2010
2010

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(8 citation statements)
references
References 26 publications
2
6
0
Order By: Relevance
“…A direct relationship was found between the impaired septal perfusion reserve and exercise capacity (septal MBFR 1.915+0.016 percentage of predicted workload, r=0.312, p=0.023). This is consistent with the findings in dogs with experimentally induced RVH 24. Contrary to the present study and the aforementioned positron emission tomography perfusion study, a single-photon emission CT study has found a surprising discrepancy between perfusion defects and exercise tolerance 33.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…A direct relationship was found between the impaired septal perfusion reserve and exercise capacity (septal MBFR 1.915+0.016 percentage of predicted workload, r=0.312, p=0.023). This is consistent with the findings in dogs with experimentally induced RVH 24. Contrary to the present study and the aforementioned positron emission tomography perfusion study, a single-photon emission CT study has found a surprising discrepancy between perfusion defects and exercise tolerance 33.…”
Section: Discussionsupporting
confidence: 91%
“…In dogs with RVH due to pressure overload, the microvascular density and its cross-sectional area are decreased 24. At the capillary level, this may result in an increase in the diffusion distance for oxygen to the mitochondria 25.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also unlikely that the CCRA-induced decrease in right coronary blood flow was the result of an increase in systolic extravascular compressive forces (Sabiston and Gregg, 1957). Unlike the left coronary circulation, significant perfusion of the normal right coronary artery occurs during both diastole and systole (Lowensohn et al, 1976;Murray and Vatner, 1981a), indicating that the effects of systolic extravascular compression are less prominent in the right coronary circulation. Moreover, the degree of systolic extravascular compression is largely dependent on levels of heart rate, ventricular inotropy, and afterload.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 With elevated plasma norepinephrine for 28 days, resting systolic and diastolic cardiac functions are preserved, and there are no signs of heart failure. 8,9 Whether the hypertrophied myocardium in this setting is able to respond to additional functional loads has not been examined.…”
mentioning
confidence: 99%